1992
DOI: 10.1007/bf00572591
|View full text |Cite
|
Sign up to set email alerts
|

The Lipomycetaceae, a model family for phylogenetic studies

Abstract: The Lipomycetaceae (Endomycetales) are known from the genera Dipodascopsis, Lipomyces and Zygozyma with budding anamorphic states in Myxozyma. The family is easily recognized culturally and physiologically but is phenotypically and ecologically extremely diverse. This natural taxon is phylogenetically distinct from the Saccharomycetaceae, but probably related to the Dipodascaceae. The possible evolution of the lipomycetaceous anamorphs is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…By using two more oligotrophic and nitrogen-depleted media (TMV and Brown's agar), only up to six species were be isolated. Nitrogen deficient media were previously used for the isolation of the members of the genus Lipomyces because these soil yeasts have the rare ability among yeasts to utilize nitrogen from heterocyclic compounds, such as imidazole, pyrimidine, and pyrazine [33] , [57] . These compounds were consequently included as a nitrogen source in selective media to isolate Lipomyces yeasts from soils [31] , [58] .…”
Section: Discussionmentioning
confidence: 99%
“…By using two more oligotrophic and nitrogen-depleted media (TMV and Brown's agar), only up to six species were be isolated. Nitrogen deficient media were previously used for the isolation of the members of the genus Lipomyces because these soil yeasts have the rare ability among yeasts to utilize nitrogen from heterocyclic compounds, such as imidazole, pyrimidine, and pyrazine [33] , [57] . These compounds were consequently included as a nitrogen source in selective media to isolate Lipomyces yeasts from soils [31] , [58] .…”
Section: Discussionmentioning
confidence: 99%
“…Species frequently found in soil are able to grow in media with low concentrations of nutrients (Babjeva & Gorin, 1987;Kimura et al, 1998;Vishniac, 1983). In particular, nitrogen oligotrophy is a widespread adaptation of yeasts, which enables them to colonize diverse substrates such as plant surfaces (reviewed by Fonseca & Inácio, 2006), tree fluxes (Golubev, Babjeva, & Novik, 1977) and soils (Botha, 2011 and pyrazine (LaRue & Spencer, 1968;van der Walt, 1992;Cornelissen, Botha, Conradie, & Wolfaardt, 2003). Recent studies showed that the diversity of yeasts growing on imidazole is larger and includes both asco-and basidiomycetes (Cornelissen et al, 2003;Yurkov et al, 2011;Yurkov, Wehde, et al, 2016).…”
Section: Yeast Phenotypesmentioning
confidence: 99%
“…In contrast to yeast species from the other major clades, it appears that there is no direct positive correlation between model similarity and trait similarity for yeast species from Lipomycetaceae , while the related model similarity is in the range of 0.87–0.96 and trait similarity is in the range of 0.40–0.89. When examining the environmental origins of the yeast species from Lipomycetaceae , it has been reported that species from this major clade had a widespread distribution [ 31 ] and could grow in the soil or in association with insects. Therefore, despite maintaining similar metabolic network structure, due to the close evolutionary distance, we speculated that the distinct growth environments may contribute to the trait variation found in some yeast species.…”
Section: Resultsmentioning
confidence: 99%